Cercus Electric Stimulation Enables Cockroach with Trajectory Control and Spatial Cognition Training - Li Yu; Jieliang Zhao; Yufan Song; Zhiyun Ma; Zhong Liu; Lulu Liang; Mengdi Xu; Wenzhong Wang; Shaoze Yan (Cyborg and Bionic Systems)
Cyborg insects are highly adaptable for detection and recognition assignments, achieved through the electrical stimulation of multiple organs and nerves to control their locomotion. However, it remains unclear whether these control strategies can promote memory formation in insects, thereby facilitating their training for recognition assignments. In this study, we employed a steering control strategy for cyborg insects in operant learning training of cockroaches in a T-maze. Remarkably, cockroaches developed a preference for specific maze channels after only five consecutive sessions of unilateral cercus electrical stimulation and steering behavior induction, achieving a memory score of 83.5%, outperforming traditional punishing training schemes. The experimental results confirmed the effectiveness of electrical stimulation on the cercus in improving the spatial cognition of cockroaches by inducing them to make specific choices in the maze. Our study revealed that the artificial locomotion control strategy can not only prompt insects to execute predetermined locomotion but also facilitate the formation of preferential memory for specific trajectories. Overall, our study highlights the electrical stimulation of sensory organs as a robust and efficient training protocol for spatial recognition learning in insects.